Morfometria e a ocorrência de hiperqueratose em tetos de vacas gir e mestiças ½ holandês e 1/2 gir - Abreu, Morgana Pontes (2019)
Mastitis is the most prevalent disease in dairy cattle, leading to substantial production losses and having a multifactorial etiology. Its occurrence in herds is associated with the health of the animal, environment, and management practices. Numerous risk factors have been described for the disease, one of which is hyperkeratosis. This condition is characterized by the accumulation of large amounts of keratin and the proliferation of corneal tissue, primarily due to mechanical forces exerted by milking equipment. Thus, the objective of this study was to evaluate teat morphometry, the occurrence of hyperkeratosis, somatic cell counts, and the correlation of these parameters with zootechnical data in 269 dairy cows (47 Gir and 222 1/2 Girolando) from the same farm. Following approval by the Animal Use Ethics Committee (CEUA) under protocol number 054/18, data were compiled on breed, number of lactations, days post-partum, peak milk production in the current lactation, somatic cell count, teat length, width, and hyperkeratosis. Hyperkeratosis was classified in scores, with scores one and two considered mild, and three and four severe. One anterior and one posterior teat of each cow, always contralateral, were evaluated. The data were tabulated in Excel 2010® and analyzed in R® using Analysis of Variance, Binary Logistic Regression, and odds ratio tests, with a significance level of 5%. No difference was found in teat length between Gir and Girolando cows; however, Gir cows had wider teats than Girolando cows. Girolando teats and cows showed a higher likelihood of developing severe hyperkeratosis compared to Gir cows. Anterior teats had a 68% higher chance of developing severe hyperkeratosis. Regarding length, the longer the teat, the greater the chance of severe hyperkeratosis, regardless of breed. Zootechnical data showed differences only for lactation period and number of lactations. Cows with two or more lactations were more likely to develop severe hyperkeratosis than primiparous cows, and the longer the postpartum period, the greater the occurrence of severe hyperkeratosis. In conclusion, on the same farm, 1/2 Girolando cows are more susceptible to severe hyperkeratosis than Gir cows.